2021
DOI: 10.3390/antibiotics10081015
|View full text |Cite
|
Sign up to set email alerts
|

Phage Targeting Streptococcus mutans In Vitro and In Vivo as a Caries-Preventive Modality

Abstract: Dental caries is a common infectious disease worldwide. Current conventional therapies lack specific antimicrobial effects against Streptococcus mutans, a key bacterium that induces caries. A promising alternative approach is bacteriophage (phage) therapy. Recently, SMHBZ8 phage targeting S. mutans was isolated and characterized. The aim of this study was to evaluate the caries-prevention efficacy of SMHBZ8 using in vitro and in vivo caries models. Hemi-mandibles dissected from euthanized healthy mice were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Notably, microbial richness was higher in old mice than in adult mice, and the genera Streptococcus , Fusobacterium , Corynebacterium , Stenotrophomonas and Enterococcus were proportionally enriched in old mice (), which is in accordance with a previous study [78]. Oral pathogenic microorganisms such as Streptococcus mutans (as the main bacterial agent for dental caries) [65, 66], and Fusobacterium nucleatum (as a periodontitis pathogen) [67, 68] have been detected more frequently in the ageing groups [79]. This evidence highlights that with increasing age, changes in the ecology of the oral cavity are associated with a risk of oral diseases [80].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Notably, microbial richness was higher in old mice than in adult mice, and the genera Streptococcus , Fusobacterium , Corynebacterium , Stenotrophomonas and Enterococcus were proportionally enriched in old mice (), which is in accordance with a previous study [78]. Oral pathogenic microorganisms such as Streptococcus mutans (as the main bacterial agent for dental caries) [65, 66], and Fusobacterium nucleatum (as a periodontitis pathogen) [67, 68] have been detected more frequently in the ageing groups [79]. This evidence highlights that with increasing age, changes in the ecology of the oral cavity are associated with a risk of oral diseases [80].…”
Section: Discussionsupporting
confidence: 82%
“…5f-j), which is in accordance with a previous study [78]. Oral pathogenic microorganisms such as Streptococcus mutans (as the main bacterial agent for dental caries) [65,66], and Fusobacterium nucleatum (as a periodontitis pathogen) [67,68] have been detected more frequently in the ageing groups [79]. This evidence highlights that with increasing age, changes in the ecology of the oral cavity are associated with a risk of oral diseases [80].…”
Section: Crosstalk Among the Oral Microbiome: The Age-related Hypothesissupporting
confidence: 88%
See 1 more Smart Citation
“…Phage therapy makes use of strictly lytic phages and is regarded as a novel method for the prevention, control, and treatment of oral infectious diseases (Shlezinger et al, 2017;Harada et al, 2018). The construction of a bacteriophage T4 RNA ligase 1 (T4 Rnl1) expressing system in S. mutans showed that T4 Rnl1 exerts membrane-directed antimicrobial activity against S. mutans and affects the spatial structure of its extracellular polysaccharide (Chen J. et al, 2020;Wolfoviz-Zilberman et al, 2021). Therefore, phages can be used as a new preventive treatment for caries.…”
Section: Phage Therapymentioning
confidence: 99%
“…Next, 1 mL of diluted intraperitoneal fluid was cultured on NA media with the pouring agar method into a sterile petri dish and then added 15 mL of NA agar medium at 40-45 °C. After it solidified, plates were incubated at 37 °C for 24 h. Then, bacterial colonies were counted using the total plate count (TPC) method [24,29].…”
Section: Test Animal Treatmentmentioning
confidence: 99%